Comparison of Clinical Outcome of Facial Artery Myomucosal Flap and Tongue Flap for Closure of Large Anterior Palatal Fistulas. Issue 6 (September 2016) - Sohail, Muhammad; Bashir, Muhammad Mustehsan; Khan, Farid Ahmad; Ashraf, Noreen
Abstract : Abstract: Closure of large anterior palatal fistula has high recurrence rate. The objective of this study was to compare the clinical outcome of facial artery myomucosal flap (FAMM flap) and tongue flap used for closure of large anterior palatal fistula. This study was conducted from March 2008 to March 2014. Thirty-nine patients, aged 2 to 40 years, who had anterior palatal fistula 5 to 20 mm in width with associated alveolar cleft and repaired with either a tongue flap or FAMM flap were included. Patients were excluded if they had adequate local palatal tissue for closure, mid, posterior or multiple fistulae, fistula width >20 mm. Closure was performed in 2 layers. Turndown flap of oral mucoperiosteum was used to reconstruct nasal layer and oral layer was reconstructed with FAMM flap in 16 and tongue flap in 23 patients. Mean(SD) pain score was 3(1) and 7(1) in FAMM flap and tongue flap groups respectively with a P value <0.096. All patients in tongue flap group experienced difficulty in speaking and eating whereas in FAMM flap group 2 had eating problem and 2 experienced speech difficulty. Mean(SD) total operative times for FAMM flap and tongue flap were 155(38) and 242(10) minutes, respectively, P value <0.002. There was no difference for other complications and no recurrence at 1 year follow-up in both groups. The authors concluded that FAMM flap should be considered first choice for closure of large anterior palatal fistulas associated with alveolar cleft as it requires less total operative time and has less early postoperative complications.